Measurement of the Emission Spectra of Protein Solutions in the Infrared Range. Description of the Method and Testing Using Solution of Human Interferon Gamma as an Example - Penkov, Nikita; Penkova, Nadezda (Frontiers in Physics, 2020)
This paper describes a new method for measuring the spectra of infrared radiation emitted by protein solutions in the native state without any external excitation. Radiation is detected using a vacuum Fourier-transform infrared spectrometer, and the tested sample itself is a source of radiation. The necessary conditions for detecting radiation from a sample are the use of a highly sensitive cooled detector and the presence of a cold background. In this work, the background was a black body at the boiling point of nitrogen. It is also important to select the optimal vacuum pumping depth for the spectrometer and sample thickness. Radiation occurs due to spontaneous radiative transitions from excited vibrational energy states to the ground state of molecules. The intensity of radiation is determined by the population of the respective energy states, which, according to the Boltzmann distribution, depends on temperature and frequency. Using solution of human interferon gamma as an example, it has been shown for the first time that proteins have intrinsic radiation. The described method allows detecting spectral lines with a radiation power of about 10−8 W or even less. It has also been demonstrated that emission spectroscopy offers advantages in the signal-to-noize ratio compared to absorption spectroscopy and allows analyzing the structural characteristics of a protein, in particular, providing information about its secondary structure. Another significant advantage of the method described in the article is its noninvasiveness. At the sample temperature of 25°С, emission spectra can be detected in the range from 400 to 3,600 cm−1, which covers almost the entire frequency range of existing stretching and bending vibrations of molecules. At the same time, in the fingerprint region from 500 to 1,600 cm−1 (the most informative part of the infrared spectrum), the highest sensitivity of the method is demonstrated. There is also potential for extending the available frequency range into the far infrared and terahertz ranges. Being applicable to the study of protein solutions in low concentrations, the proposed approach is not only interesting from the point of view of fundamental science but also can have applied significance in biological and medical research.